2008
DOI: 10.1289/ehp.10943
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Living Near Roadways on Spirometry and Exhaled Nitric Oxide in Elementary Schoolchildren

Abstract: BackgroundLiving near major roadways has been associated with an increase in respiratory symptoms, but little is known about how this relates to airway inflammation.ObjectiveWe assessed the effects of living near local residential roadways based on objective indicators of ventilatory function and airway inflammation.MethodsWe estimated ambient air pollution, resolved to the level of the child’s neighborhood, using a land-use regression model for children 9–11 years of age. We also summed the length of roadways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 34 publications
1
58
3
Order By: Relevance
“…FE NO has been related to the exposure to particles, NO 2 and ozone, measured either by personal or by ambient monitors in panel studies of children with asthma and in healthy children (6,28,29). Moreover, FE NO levels have been found to be elevated in the children living in areas characterized by high traffic exposure (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…FE NO has been related to the exposure to particles, NO 2 and ozone, measured either by personal or by ambient monitors in panel studies of children with asthma and in healthy children (6,28,29). Moreover, FE NO levels have been found to be elevated in the children living in areas characterized by high traffic exposure (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…WOEAS recruited 50 participants from the Windsor Children's Respiratory Health Study. 31,32 Participation was limited to children between the ages of 10 and 13 who had physician diagnosed asthma. Health data collection was concurrent with air monitoring for all study participants, with daily lung function and questionnaire data collected for a total of 5 days in winter and 5 days in summer.…”
Section: Health Datamentioning
confidence: 99%
“…For each measurement, participants were instructed to collect three flow readings. As described by Dales et al, 31,32 the maximum of the three readings was used for the analyses reported in this paper. Study design and protocols were approved by Health Canada's Research Ethics Board and all personal information is protected according to the Access to Information and Privacy Acts.…”
Section: Health Datamentioning
confidence: 99%
“…Proximity to major roads, a surrogate of traffic exposure, has been associated with decreased lung growth (3), increased asthma symptoms (4), increased airway inflammatory markers including exhaled nitric oxide (5), and increased oxidative stress markers (6).The association between exposure to air pollution and development of asthma, however, is less clear, although recent research has found incident asthma to be associated with exposure to traffic-related air pollution (7). Air pollution in urban areas is a complex mixture of particles and gas-phase pollutants arising from a myriad of sources.…”
mentioning
confidence: 99%